The characterization of NiO-CoO/MgO catalyst for autothermal reforming of methane - Kusworo, Tutuk Djoko; Songip, A R; Amin, N A. Saidina (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2005)
The characterization of NiO-CoO/MgO catalyst for autothermal reforming of methaneThe drawback of conventional reforming of methane such as partial oxidation and steam reforming was carbon formation. The research was developed a suitable catalyst for combination of partial and steam reforming of methane and called autothermal reforming to reduce the coke formation. The NiO-CoO/MgO catalysts were prepared by an impregnation method and characterized by Temperature Programmed Reduction (TPR), X-ray Diffraction (XRD) and Thermal Gravitymetry Analysis (TGA). The TPR and XRD results reveal that the catalyst characteristic is strongly influenced by the Co/Ni ratio. From TPR and TGA analysis, the sintering phenomena did not occur in the autothermal reforming of methane. The results reveal that Co/Ni ratios have a small effect in the catalytic activity for autothermal reforming. Nevertheless, the catalyst showed an optimum performance in this process when its Co/Ni ratio was 0.75.Â Keywords: Autothermal ReformingAbstrakMasalah yang terjadi pada proses konvensional reformasi metana seperti oksidasi parsial metana dan reformasi kukus adalah pembentukan karbon. Penelitian yang dilakukan adalah mengembangkan katalis yang sesuai untuk gabungan proses oksidasi parsial dan reformasi kukus atau yang disebut reformasi metana secara autothermal. Katalis NiO-CoO/MgO yang digunakan dibuat dengan metode impregnasi dan dilakukan pengujian dengan TPR, XRD dan TGA untuk mengetahui sifat-sifat dari katalis tersebut. Hasil TPR dan XRD menunjukkan bahwa karakteristik dari katalis sangat dipengaruhi oleh perbandingan CoiN i. Hasil pengamatan TPR dan TGA menunjukan bahwa sintering tidak terjadi di dalam proses reformasi metana secara autothermal. Hasil eksperimen juga menunjukan bahwa perbandingan Co/Ni hanya kecil pengaruhnya pada unjuk kerja katalis. Namun demikian katalis menunjukan unjuk kerja yang optimum pada perbandingan CoiN i = 0.75.Â Kata Kunci: Reformasi Autothermal